[English translation] Capacity of a sweat patch method to detect the effect of an antiperspirant - Aburto Corona, Jorge Alberto (2025)
An effective antiperspirant is supposed to reduce sweat production by up to 50%, according to the manufacturers, but the scientific evidence in the literature is limited; possibly, the actual reduction may be so small that it may not be detected by conventional methods. The purpose of this study was to verify if the sweat patch method was able to detect the reduction in regional sweat loss that would be expected from using an antiperspirant. In addition, the magnitude of the effect was quantified. We verified the impact of an antiperspirant (condition A, skin treated with the product) on localized scapular sweat rate during 20 minutes of exercise at 78-80% HRmax, at 29.7 ± 0.5°C ambient temperature and 54 ± 3.4% relative humidity, compared with a control condition (C, untreated skin). A statistically significant difference in scapular sweat rate was found between conditions: A = 14.6 ± 10.3 μL * min(-1)  and C = 19.2± 12.6 μL * min(-1)  (p = 0.001). This means that the participants secreted approximately 24% less sweat when using an antiperspirant, compared with the intact skin, as measured by the sweat patch method.